Leadership for the Common Good - Barbara C. Chosby, John M. Bryson (Jossey-Bass, 2005)
When it was first published in 1992, the first edition of Leadership for the Common Good presented a revolutionary approach to community and organizational leadership in a shared-power world. Now, in this completely revised and updated edition, Barbara Crosby and John Bryson expand on their proven leadership model and offer new insights and guidance to leaders. This second edition is a practical resource for a new generation of leaders and aspiring leaders and includes success stories, challenges, and real-world experience.